Passive acoustic monitoring of bed load discharge in a large gravel bed river. Issue 2 (23rd February 2017) - Geay, T.; Belleudy, P.; Gervaise, C.; Habersack, H.; Aigner, J.; Kreisler, A.; Seitz, H.; Laronne, J. B.
Abstract: Surrogate technologies to monitor bed load discharge have been developed to supplement and ultimately take over traditional direct methods. Our research deals with passive acoustic monitoring of bed load flux using a hydrophone continuously deployed near a river bed. This passive acoustic technology senses any acoustic waves propagated in the river environment and particularly the sound due to interparticle collisions emitted during bed load movement. A data set has been acquired in the large Alpine gravel‐bedded Drau River. Analysis of the short‐term frequency response of acoustic signals allows us to determine the origin of recorded noises and to consider their frequency variations. Results are compared with ancillary field data of water depth and bed load transport inferred from the signals of a geophone array. Hydrophone and geophone signals are well correlated. Thanks to the large network of deployed geophones, analysis of the spatial resolution of hydrophone measurements shows that the sensor is sensitive to bed load motion not only locally but over distances of 5–10 m (10–20% of river width). Our results are promising in terms of the potential use of hydrophones for monitoring bed load transport in large gravel bed rivers: acoustic signals represent a large river bed area, rather than being local; hydrophones can be installed in large floods; they can be deployed at a low cost and provide continuous monitoring at high temporal resolution. Key Points: Hydrophone signals in a large gravel bed river are correlated to bed load discharge monitored by geophones The listening distance of a hydrophone is estimated at 5 to 10 m Passive acoustic signals recorded in a large gravel bed river are processed using short‐term frequency representations